Exploring the inflammatory profile of homelessness population: a comprehensive analysis of individuals in two temporary shelters in Lisbon - Gomes, Ana T. P. C.; Mendes, Karina; Ferrito, Cândida; Andrade, Filipa; Neves-Amado, João; Resende, Ana; Santos, Paulo; Manso, Dina; Almeida, António; Vollrath, Antónia; Lopes, Rafaela; Barros, Marlene; et al. (Frontiers in Public Health, 2024)
Background Homeless people are continuously facing adverse living conditions as poor access to basic nutrition, hygiene conditions and healthcare services, being at increased risk of severe infectious diseases as HIV and hepatitis as well as cardiovascular diseases and mental disorders. The characterization of homeless people’s health is fundamental to identify their health care needs. Considering that the aforementioned diseases are associated with chronic inflammatory processes, the main goal of this study was to characterize the inflammatory profile of a homeless population through quantification in saliva of a panel of inflammatory cytokines. Methods The inflammatory profile was assessed in 114 individuals residing in two temporary shelters located in Lisbon and that accepted to participated in the study. Inflammatory proteins were quantified using a Multiplex Immunoassay approach. Data analysis was performed using the GraphPad Prism software and statistical significance among the groups was assessed using the nonparametric Mann–Whitney test. Results Even though some protein levels might be masked by drug treatment, data analysis showed high levels of INF-ϒ, IL-10 and TNF-α in the infectious disease group, critical cytokines for the immune response against viruses and bacteria. Also, cytokines like IL-1β and IL-6 were detected at statistically significant levels in the cardiovascular disease group and all cytokines included in this study were quantified in the mental disorders group. Conclusion These findings may help the healthcare services in the evaluation of treatment efficacy and disease monitoring, and in the development of effective public healthcare strategies and policy interventions to improve quality of life of the homeless population.